A review on the effect of macrocyclic lactones on dung-dwelling insects: Toxicity of macrocyclic lactones to dung beetles - Jacobs, Carmen T. (Onderstepoort J Vet Res, 2015)
Avermectins and milbemycins are commonly used in agro-ecosystems for the control of parasites in domestic livestock. As integral members of agro-ecosystems with importance in maintaining pasture health through dung burial behaviour, dung beetles are an excellent non-target bio-indicator taxon for examining potential detrimental effects of pesticide application. The current review focuses on the relative toxicity of four different anthelmintics (ivermectin, eprinomectin, doramectin and moxidectin) in dung residues using dung beetles as a bio-indicator species. One of the implications of this review is that there could be an effect that extends to the entire natural assemblage of insects inhabiting and feeding on the dung of cattle treated with avermectin or milbemycin products. Over time, reduced reproductive rate would result in decreased dung beetle populations and ultimately, a decrease in the rate of dung degradation and dung burial.